Kajian Spiritualitas di Tempat Kerja pada Konteks Organisasi Bisnis - Leo Agung Manggala Yogatama; Nilam Widyarini (Jurnal Psikologi, 2015)
Spirituality at workplace is a new topic in organizational psychology. Spirituality at workplace is related to a construction that indicates an increase of quality performance. The purpose of this study was to find the factors forming the spiritual climate in Indonesian organizational context. The subjects were 417 employees of a media company. The method used in this study was exploratory factor analysis. The results indicated that there were two factors forming the spiritual climate in the workplace, namely vision and mission that motivated the employees and made them connected with their purposes at work, and the second factor was employees’ deep concern of their lives. This study can be used as practical guidance to establish a healthy working climate in organization.